Temperature compensation strategies for SHM based on electromechanical impedance: a comparative study - Dias, Lorena Lopes; Gonsalez-Bueno, Camila Gianini [UNESP]; Lopes, Kayc Wayhs; Bueno, Douglas Domingues [UNESP] (ABCM, 2022)
Different structures are subjected to operational and external effects which can generate structural damage. The structural performance must be carefully designed to avoid failures due to their consequences typically involve economic, social and environmental impacts. Damage detection is then one of the great concerns of the engineers, who have carried out numerous researches to develop techniques in the field of structural health monitoring (SHM). Among different techniques, Electromechanical Impedance (EMI) approach has attracted attention due to its important and promising aspects. However, the sensitivity of this technique is related to environmental conditions fluctuations, which can lead to false diagnoses, and the temperature is one of the most critical factors for EMI technique. In this point of view, several researchers have developed compensation methods in order to minimize the effects caused by temperature variation in impedance curves. In this context, the present article provides a comparative study involving two different temperature compensation strategies by employing experimental data measured for an aluminum beam on three different conditions: i) without damage, ii) with a damage characterized by an addition of small mass and iii) another one by an introduced mechanical cut on the beam. The results obtained indicate that those two techniques investigated are able to minimize the temperature effect in the studied system, and one of them presents a better performance to reduce false alarms in damage detections using the eletromechanical impedance technique.
Estratégias de compensação de temperatura para SHM baseadas em impedância eletromecânica: um estudo comparativo
Keywords: Structural health monitoring; Electromechanical impedance; Comparative study; Temperature compensation techniques; Aluminum beam